Production and Soil Responses to Intercropping of Forage Grasses with Corn and Soybean Silage. (1st November 2016) - Pariz, Cristiano M.; Costa, Ciniro; Crusciol, Carlos A. C.; Meirelles, Paulo R. L.; Castilhos, André M.; Andreotti, Marcelo; Costa, Nídia R.; Martello, Jorge M.; Souza, Daniel M.; Sarto, Jaqueline R. W.; Franzluebbers, Alan J.
Abstract : Agricultural management systems are needed to simultaneously enhance production, and improve soil quality. We investigated the effects of intercropped grass on production of corn ( Zea mays L.) harvested for silage at 0.20 and 0.45 m height in the summer, as well as on production of subsequent forage, silage soybean [ Glycine max (L.) Merr.], and soil responses on a Typic Haplorthox in Botucatu, SP, Brazil. Palisade grass [ Urochloa brizantha (Hochst. ex A. Rich.) R. Webster 'Marandu'] was the introduced companion crop with corn (Years 1 and 2), while signal grass [ Urochloa decumbens (Stapf) R. Webster 'Basilisk'] was the residual weedy species in comparison. Guinea grass [ Urochloa maxima (Jacq.) R. Webster 'Aruãna'] was the introduced companion crop with soybean (Year 3), with only a residual effect of crop systems from the previous 2 yr. When cut at 0.45 m compared with 0.20 m height, corn intercropped with palisade grass had greater leaf nutrient concentrations, agronomic characteristics, forage mass of pasture for grazing by lambs ( Ovis aries ), greater surface mulch produced, and greater quantity of N, P, and K returned to soil. Greater soil organic matter, P, K, and Mg concentration, and base saturation in the surface soil depth and lower soil penetration resistance at all depths occurred at 0.45 m than at 0.20 m corn silage cutting height intercropped with palisade grass. Analyzing the system as a whole, harvesting corn silage crop with palisade grass intercrop at 0.45 m height was the most viable option in this integrated crop–livestock system (ICLS). Core Ideas Agricultural management systems are needed to enhance production and improve soil quality. After corn silage harvest, pasture was grazed by lambs in winter/spring using a semi‐feedlot system. Harvesting corn silage crop with palisade grass intercrop at 0.45 m height was the most viable option.